Development and usability evaluation of the pedialysis mobile application for teaching and evaluation of pediatric patients on dialysis (Research, Society and Development, 2021)
The prevalence of chronic kidney disease (CKD) has increased worldwide, as well as the costs of adequate treatment. The choice of dialysis method between hemodialysis and peritoneal dialysis depends on variables such as age and weight, hemodynamic conditions, presence of previous abdominal surgery or current severe abdominal diseases, in addition to the availability of therapy in the hospital and training of professionals. The use of apps appears as an aid, minimizing misdiagnosis, as well as an important tool to the proper conduct of selection of the appropriate catheter and vessel, study of the causes of renal failure, follow-up of important exams and rational antimicrobial therapy. We developed a national mobile application, for Android system, which works without internet connection and has no cost to the user, for monitoring CKD and dialysis in pediatrics, aimed at teaching medical students. To assess usability, we used the SUS scale (System Usability Scale) applied to 9 students and 12 teachers, in addition to 16 students who responded to the case without using the application (controls). The project was submitted via the Brazil platform and approved by the Institution's Ethics and Research Committee. An Informed Consent Form (ICF) was applied to all participants. Data analysis showed an average SUS scale of 74,5 points, considered good in terms of interface. The application was also well evaluated, being praised by users. It is concluded that the application presented excellent usability results, being able to help students and professionals in the teaching of nephropediatrics.